PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN DAN KINERJA SAHAM PADA INDEKS SAHAM LQ45 - Rachmaniar Myrianda Dwiputri (Jurnal Ekonomi dan Industri, 2019)
The aim of the company is to get a profit, so the company can be run properly as it should. The management of the company cannot necessarily do various ways to achieve this goal by itself, there are internal and external interests that will directly or indirectly affect the management. Companies are required to follow applicable rules to minimize conflicts of interest within the company. These rules are outlined in the Implementation of Corporate Governance. It is expected that with the implementation of Good Corporate Governance, it will improve the company's performance, especially the financial performance and performance of the company's shares. Therefore, this study aims to look at the influence of good corporate governance on financial performance and the performance of the company’s shares. This research used a purposive sampling method in selecting samples and research samples are 45 companies indexed by LQ45 shares in the period of August 2016 - January 2017. Data used are secondary data and the variables used in this study are the financial ratios of DAR, DER, NPM, ROA, ROE, EPS, and PBV. In addition, the variables of Good Corporate Governance consist of Size of Commissioners, Independent Commissioners, Concentrated Ownership, and Proportion of Independent Commissioners. The relationship between variables of Corporate Governance, Financial Performance, and Stock Performance was tested using Structural Equation Modeling (SEM). The results found that Corporate Governance did not have a significant effect and positively related to the Financial Performance and Stock Performance of the LQ45 index company for the period of August 2016 - January 2017. While the Financial Performance significantly affected the direction of the positive relationship to Stock Performance